Характеристика генетичної структури населення України за поліморфними варіантами генів системи детоксикації ксенобіотиків - Левкович, Н.М.; Горовенко, Н.Г. (Фактори експериментальної еволюції організмів, 2014)
Aims. Determine the genotype frequencies for the most prevalent polymorphic variants of of xenobiotic detoxification genes (CYP2C9, CYP2C19, CYP2D6 and MDR1) in the Ukrainian population for the practical implementation of drugs individualizing use and in the calculation of the multifactorial diseases risk. Methods. 918 Ukrainian were genotyped for major polymorphic variants of xenobiotic detoxification genes. Genotyping was performed using of allele-specific polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) methods. Results. Provided data characterizing the genotypes frequency of the studied polymorphic variants of CYP2C9, CYP2C19, CYP2D6 and MDR1 genes in the Ukrainian population. It’s proved the absence of significant differences in the distribution of received genotype frequency compared with other Europeans. Conclusions. Obtained data justify the use of listed polymorphic variants for study as prognostic pharmacogenetic markers in individualizing drugs therapy.